Prognostic value of growth differentiation factor-15 in patients with coronary artery disease: A meta-analysis and systematic review - Zhang, Song; Hao, Panpan; Li, Jiaxin; Zhang, Qi; Yin, Xiaoying; Wang, Jiali; Chen, Yuguo (Frontiers in Cardiovascular Medicine, 2023)
Background and Aims: The predictive value of growth differentiation factor-15 (GDF-15) for individual cardiovascular outcomes remained controversial in patients with coronary artery disease (CAD). We aimed to investigate the effects of GDF-15 on all-cause death, cardiovascular death, MI and stroke in CAD patients. Methods: We searched PubMed, EMBASE, Cochrane library and Web of Science till 30 December, 2020. Hazard ratios (HRs) were combined with fixed or random effect meta-analyses. Subgroup analyses were performed in different disease types. Sensitivity analyses were used to evaluate the stability of the results. Publication bias was tested using funnel plots. Results: A total of 10 studies with 49,443 patients were included in this meta-analysis. Patients with the highest GDF-15 concentrations had significantly increased risk of all-cause death (HR 2.24; 95% CI 1.95-2.57), cardiovascular death (HR 2.00; 95% CI 1.66-2.42), MI (HR 1.42; 95% CI 1.21-1.66) after adjusting clinical characteristics and prognostic biomarkers (hs-TnT, cystatin C, hs-CRP, and NT-proBNP) but except for stroke (HR 1.43; 95% CI 1.01-2.03, P=0.05). For the outcome of all-cause death and cardiovascular death, subgroup analyses revealed consistent results. Sensitivity analyses showed that the results were stable. Funnel plots showed that there was no publication bias. Conclusions: In CAD patients with elevated GDF-15 levels on admission, there were independently significant risks for all-cause death and cardiovascular death. The highest concentrations of GDF-15 had a lower predictive effect on MI than all-cause death and cardiovascular death. The association of GDF-15 with the outcome of stroke needs to be further studied.